Fuzzy Logic in Human Reasoning - Michael Gr. Voskoglou (Bulletin of Electrical Engineering and Informatics, 2013)
Reasoning, the most important human brain operation, is characterized by a degree of fuzziness and uncertainty. In this paper we construct a fuzzy model for the reasoning process giving, through the calculation of probabilities and possibilities of all possible individuals’ profiles, a quantitative/qualitative view of their behaviour during the process. In this model the main stages of human reasoning (imagination, visualisation and generation of ideas) are represented as fuzzy subsets of   set of linguistic labels characterizing a person’s performance in each stage. Further, using the coordinates of the centre of mass of the graph of the corresponding membership function we develop a method of measuring the reasoning skills of a group of individuals. We also present a number of classroom experiments with student groups’ of our institution (T. E. I. of Patras, Greece) illustrating our results in practice.